Efeitos diretos e indiretos das formigas cortadeiras de folha (Atta) sobre a dinâmica da vegetação em uma savana neotropical - Costa, Alan Nilo da (2013)
Ants are fundamental organisms in the dynamics of several terrestrial ecosystems. In the Neotropical region, leaf-cutting ants detach because their herbivory activity and nest construction have direct and indirect effects on grow, reproduction and survivor of plants. However, the impact of these effects on the dynamics of seedling recruitment remains poorly investigated for the majority of leaf-cutting ants species in many ecosystems. This study examined if herbivory and nest construction by leaf-cutting ants of the Atta genus, could modify the vegetation structure and dynamics in a Brazilian Cerrado, a savanna ecosystem. More specificly, it determined if (a) the foraging activity of leaf-cutting ants have negative impacts in seedling recruitment, (b) nest modify the environmental conditions and (c) the possible changes return different vegetation patterns (abundance and richness) on Atta nest mounds in some Cerrado´s physiognomies. The results present that diaspore removal is higher at areas with leaf-cutting ants and consume of diaspores by this insects correspond one/third of the total removal at ground level. In addition, defoliation by leaf-cutting ants is more intense than by others herbivores, but just some species shown less survivor rates in unclosed seedling to Atta foraging. At all physiognomy studied (cerrado ralo, cerrado denso and mata semidecídua), nest construction and maintenance produced significant modifications on soil conditions on mound nest, including reduction of litterfall biomass, alteration of resistance to penetration, elevation of temperature, less humidity and low nutrients concentration (N, P e K), when compared with surrounding area. Also sample plots on active nests had different vegetation patterns, less abundance and richness of both small (height < 20 cm) and large plants (20 120 cm) on nest, when compared to the surrounding area. Abandoned nest and surrounding area had similar abundance of small plants, but species richness of small plants and abundance/richness of large plants was still reduced on nests. In the experiments with vegetation dynamics, it was possible to observe a tendency of reduction in emergency and a pronounced mortality of seedling on activity nests. The negative impact of nests on seedling recruitment appear to come from the less mild micro-climate conditions, intense defoliation and burial, while low nutrients concentration had no significant effects. The findings in this study indicate that intense foraging activity and nest presence may reduce the seedling recruitment in savanna environment and reinforce the relevance of leaf-cutting, and possibly of others organisms, on vegetation dynamics in the Cerrado.